Biomechanical and finite element analyses of bone cement‐Injectable cannulated pedicle screw fixation in osteoporotic bone. Issue 5 (15th May 2015) - Liu, Yaoyao; Xu, Jianzhong; Sun, Dong; Luo, Fei; Zhang, Zehua; Dai, Fei
Abstract: The objectives of this study were to investigate the safety and biomechanical stability of a polymethylmethacrylate (PMMA)‐augmented bone cement‐injectable cannulated pedicle screw (CICPS) in cancellous bone model, and to analyze the stress distribution at the screw‐cement‐bone interface. The OMEGA cannulated pedicle screw (OPS) and conventional pedicle screw (CPS) were used as control groups. Safety of the CICPS was evaluated by the static bending and bending fatigue tests. Biomechanical stability was analyzed by the maximum axial pullout strength and maximum torque tests. Stress distribution at the screw–cement–bone interface was analyzed by the finite element (FE) method. The CICPS and CPS produced statistically similar values for bending stiffness, bending structural stiffness, and bending yield moment. The maximum pullout force was 53.47 ± 8.65 N in CPS group, compared to 130.82 ± 7.32 N and 175.45 ± 43.01 N in the PMMA‐augmented OPS and CICPS groups, respectively ( p  < 0.05). The CICPS had a significantly greater torque than the OPS and CPS. The FE model did not reveal excessive stress at the screw‐cement‐bone interface in the CICPS group. In conclusion, PMMA‐augmentation with CICPS may be a potentially useful method to increase the stability of pedicle screws in patients with osteoporosis. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 960–967, 2016.